Calcifying coccolithophore: an evolutionary advantage against extracellular oxidative damage - Yang, M; Batchelor-McAuley, C; Barton, S; Rickaby, REM; Bouman, HA; Compton, RG (Wiley, 2023)
The evolutionary advantages afforded by phytoplankton calcification remain enigmatic. In this work, fluoroelectrochemical experiments reveal that the presence of a CaCO3 shell of a naturally calcifying coccolithophore, Coccolithus braarudii, offers protection against extracellular oxidants as measured by the time required for the switch-off in their chlorophyll signal, compared to the deshelled equivalents, suggesting the shift toward calcification offers some advantages for survival in the surface of radical-rich seawater.